Cysteinyl-tRNA synthetase governs cysteine polysulfidation and mitochondrial bioenergetics. Issue 1 (December 2017) - Akaike, Takaaki; Ida, Tomoaki; Wei, Fan-Yan; Nishida, Motohiro; Kumagai, Yoshito; Alam, Md. Morshedul; Ihara, Hideshi; Sawa, Tomohiro; Matsunaga, Tetsuro; Kasamatsu, Shingo; Nishimura, Akiyuki; Morita, Masanobu; et al.
Abstract Cysteine hydropersulfide (CysSSH) occurs in abundant quantities in various organisms, yet little is known about its biosynthesis and physiological functions. Extensive persulfide formation is apparent in cysteine-containing proteins inEscherichia coli and mammalian cells and is believed to result from post-translational processes involving hydrogen sulfide-related chemistry. Here we demonstrate effective CysSSH synthesis from the substratel -cysteine, a reaction catalyzed by prokaryotic and mammalian cysteinyl-tRNA synthetases (CARSs). Targeted disruption of the genes encoding mitochondrial CARSs in mice and human cells shows that CARSs have a crucial role in endogenous CysSSH production and suggests that these enzymes serve as the principal cysteine persulfide synthases in vivo. CARSs also catalyze co-translational cysteine polysulfidation and are involved in the regulation of mitochondrial biogenesis and bioenergetics. Investigating CARS-dependent persulfide production may thus clarify aberrant redox signaling in physiological and pathophysiological conditions, and suggest therapeutic targets based on oxidative stress and mitochondrial dysfunction. Cysteine hydropersulfides (CysSSH) are believed to have a cellular redox protective role. Here the authors show that these species can be produced fromL -cysteine by cysteinyl-tRNA synthetases and that these enzymes are also involved in mitochondrial biogenesis and bioenergetics regulation.